THE GREEN PLACE BUILDING FOR LOOKING BIRD AT GUANGZHOU NANSHA BIRD PARK (INFINITE 8) - Fariz Nizar; Naufal Kresna Diwangkara (urn:nbn:de:00001miji.v2i11, 2022)
This research is located in the Nansha Bird Park located in Guangzhou which has an unspoiled wetland landscape. we designed the building with the concept of "Infinite 8", this infinite 8 is a building that has no boundaries like the letter 8 that is unbroken and describes the universe. and also the number "8" on this building symbolizes good luck for most Chinese people. In this design, you will find a pillar that rises to the sky that describes the boundaries of the pole, besides that this building is made of bamboo. The method in this design concept is exploratory, namely by exploring more ideas from various things and philosophies from number 8. This building also adheres to the application of the green building principle with the observation method in the field, responding to wet land, the use of full bamboo is highly recommended for this building. from this study resulted in a design suitable for bird viewing at the Nansha Bird Park in Guangzhou China.